Specifying Clauses in the Administrative-Legal Style of 19th-Century Serbian Language - Pavlović Jovanović, Jelena M. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
The paper examines the status of specifying clauses in the administrative-legal style of the Serbian language dating back to the 19th century. The corpus includes texts from 19th-century constitutions (adopted in 1835, 1838, 1869, 1888, and 1901) and the Collection of Laws and Decrees adopted by the Principality/Kingdom of Serbia. To isolate the normative-legal and ideological layers of the texts, the analysis employs a combination of historical-linguistic, syntactic-semantic, and functional methods, as well as legal theory methodology. As a result of the recent development of the Serbian language, the specifying meaning is only found infrequently in the examined corpus. Clauses introduced by the conjunction с тим да occur in postpositions and encode information of secondary importance to administrative-legal norms. Furthermore, an online (available) search of the Legal Information System of the Republic of Serbia reveals that the specifying meaning is only marginal even in modern legal language.